An investigation of home cooking practices to deal with food-related anxieties in China: issues of embodiment and intergenerational transmission - Li, Meng (2017)
In recent decades, many Chinese have experienced changes in their eating as a result of a shift from food shortages to an expansion of food markets. Many urban Chinese make choices from a variety of food, and food safety incidents frequently reported in the media have raised consumer concerns with food quality and the potential effects of foods on human health. Meanwhile, some urban dwellers worry about overweight, hypertension, cardiovascular diseases, and other health threats as a result of, for example, diets that are high in fats and sugar. Some studies have examined how consumers respond to food-related anxieties in China. These studies have suggested that they may change their eating or shopping patterns and rely on external indicators such as, brands and vendor types. A number of these studies are based on quantitative calculations of patterns of participants’ behaviours or perceptions. However, they pay little attention to how ordinary people experience and deal with food-related anxieties. Moreover, individuals seem to be passive and dependent on institutional efforts to control food-related anxieties.